Organizational Behavior: The Investigation of Communications Effectiveness & Emotional Intelligence on Job Satisfaction (Case Study in Irans Universities) - Jorfi, Hassan; Sahar, Mahdi Elhaee (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
In today's complex global environment, communications effectiveness and emotional intelligence remains a key topic of concern among managers worldwide. The paper is undertaken to understand the relationship between managers communications effectiveness to improve emotional intelligence and job satisfaction in the universities of Iran. In current paper emotional intelligence plays main role in relationship with communication effectiveness and with job satisfaction. Data (N = 234) for this study were collected through questionnaires and the participants were managers in universities of Iran. The result in current paper shows that emotional intelligence has a positive and strong relationship with communication effectiveness and with job satisfaction.